2014
DOI: 10.5505/tjtes.2014.76399
|View full text |Cite
|
Sign up to set email alerts
|

Value of the Glasgow Coma Scale, Age, and Arterial Blood Pressure (GAP) Score for Predicting the Mortality of Major Trauma Patients Presenting to the Emergency Department

Abstract: BACKGROUND:The purpose of this study is to detect the mortality predictive power of new Glasgow coma scale, age, and arterial pressure (GAP) scoring system in major trauma patients admitted to the emergency department (ED).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
2
23

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 12 publications
(15 reference statements)
4
33
2
23
Order By: Relevance
“…When stratifying MGAP scores as low (23)(24)(25)(26)(27)(28)(29), intermediate (18)(19)(20)(21)(22) and high (3-17) risk for death, the in-hospital mortality rates were uniformly higher than in the original validation cohort of the MGAP score in France (Table 3). The area under the ROC curve for the MGAP score in the French validation cohort was 0.90, compared with 0.85 in the subset of patients with sufficient data to Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When stratifying MGAP scores as low (23)(24)(25)(26)(27)(28)(29), intermediate (18)(19)(20)(21)(22) and high (3-17) risk for death, the in-hospital mortality rates were uniformly higher than in the original validation cohort of the MGAP score in France (Table 3). The area under the ROC curve for the MGAP score in the French validation cohort was 0.90, compared with 0.85 in the subset of patients with sufficient data to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One concern is that vital sign measurements occurred at the time of hospital triage, not at a fixed interval after the injury event, which may introduce bias as vital signs fluctuate over time and with resuscitative measures. However, vital signs collected at the time of hospital arrival are routinely used for injury scoring in low-and middle-income countries without adjusting for time since injury [19,22,[26][27][28]. In fact, because physiologic scoring systems do not rely on comprehensive anatomic evaluation, they potentially provide a more feasible means of estimating injury severity in low-and middle-income countries using readily available clinic or administrative data [29].…”
Section: Discussionmentioning
confidence: 99%
“…Besides that, GAP scores are also more practical use in the field compared to RTS. 7,8 In this study it was found that there was a negative correlation with moderate strength and significance between GAP scores and the IL-6 cytokines (Pearson correlation -0.399 and p = 0.002). Yutaka Kondo et al stated that GAP score may reflect the severity of the trauma and predict mortality in trauma patients better than other trauma scoring system.…”
Section: Discussionmentioning
confidence: 84%
“…This heterogeneity has been stimulating numerous scientific researches, especially with regard to the development of Trauma Scoring Systems (TSS), which involve the attribution of a certain score to trauma victims depending on specific variables. 8,9 Trauma scoring systems may guide decisions involving both prehospital care-for example, if a specialized transport is required-and inhospital caresuch as, whether or not certain surgical procedures should be performed. In addition, TSS also provide important information concerning the anatomy of the lesions, physiological changes, and prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, TSS provide epidemiological data that may guide campaigns on trauma prevention. 9,10 Over the past years, a wide array of TSS were developed, including RTS, which considers three physiological parameters: Respiratory rate, systolic blood pressure and GCS. 11 Despite remaining widely used and discussed, the calculation of RTS involves overly complex formulas, which could delay trauma care to the patient.…”
Section: Introductionmentioning
confidence: 99%